2021
DOI: 10.1136/bmjos-2021-100202
|View full text |Cite
|
Sign up to set email alerts
|

How a few poorly designed COVID-19 studies may have contributed to misinformation in Brazil: the case for evidence-based communication of science

Abstract: How a few poorly designed COVID-19 studies may have contributed to misinformation in Brazil: the case for evidencebased communication of science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
4
0
2
Order By: Relevance
“…Após esse fato, houve a disseminação de um estudo no Brasil, afirmando que haveriam benefícios da hidroxicloroquina aliada a azitromicina em casos suspeitos de COVID-19 em estágio inicial. Este estudo teve grande repercussão, mesmo sendo apenas um arquivo de Dropbox, divulgado através das redes sociais e Whatsapp 13 . No caso da ivermectina, o estudo que parece primeiro ter chamado a atenção para o uso do medicamento, foi um estudo in vitro publicado em na revista Antiviral Research, estudo que inclusive realça as limitações dos achados in vitro 18 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Após esse fato, houve a disseminação de um estudo no Brasil, afirmando que haveriam benefícios da hidroxicloroquina aliada a azitromicina em casos suspeitos de COVID-19 em estágio inicial. Este estudo teve grande repercussão, mesmo sendo apenas um arquivo de Dropbox, divulgado através das redes sociais e Whatsapp 13 . No caso da ivermectina, o estudo que parece primeiro ter chamado a atenção para o uso do medicamento, foi um estudo in vitro publicado em na revista Antiviral Research, estudo que inclusive realça as limitações dos achados in vitro 18 .…”
Section: Discussionunclassified
“…Porém é importante ressaltar que o formato preprint, assim como outros formatos de publicação científica, podem ser utilizados de forma incorreta, seja pela publicação de dados manipulados, para fins políticos ou mesmo sensacionalismo. Diversos casos envolvendo possíveis medicamentos para combater o COVID-19, utilizaram de preprints como ferramenta para a divulgação de achados contraditórios, de estudos mal delineados, com claros erros metodológicos e vieses 13 , que chamam a atenção para a falta de integridade de alguns membros científicos e não científicos.…”
Section: Introductionunclassified
“…4 The observational studies on the effectiveness of HCQ reported divergent results, from a five-fold reduction in mortality risk to an eight-fold increased risk of intensive care unit (ICU) admission, 5,6 leading to a heated debate about the effectiveness of HCQ. [6][7][8][9][10] Today, RCTs have convincingly shown that HCQ has no benefit in the treatment of COVID-19 patients and may even be harmful. 11,12 Variation in the estimated effects of HCQ treatment and divergence from the RCT results may arise from differences between the included patient populations.…”
Section: Introductionmentioning
confidence: 99%
“… 9 - 12 This issue was the subject of investigational hearings in the Brazilian Senate, including the off-label use of hydroxychloroquine and ivermectin, among others. A recent article showed that a small set of poorly designed studies on medications played a significant role in misinformation during the COVID-19 first wave in Brazil, 13 when vaccines were still not available. In this turbulent scenario of uncertainty about the future of the pandemic combined with fear and high risk of exposure to SARS-CoV-2 in dental offices, dentists could be inclined to self-medicate or use substances without proven efficacy against COVID-19.…”
Section: Introductionmentioning
confidence: 99%